ITC-Euromaster Course Pool for AEC Engineers - Tibaut, Andrej; Rebolj, Danijel; Menzel, Karsten; Hore, Alan (International Journal of Emerging Technologies in Learning (iJET), 2013)
The paper describes the ITC-Euromaster Course Pool. It is a concept that powers e-learning environment for conducting an international Masterâ??s level programme in information technologies for Architecture, Engineering and Construction (AEC). The e-learning environment integrates resources (units of study, learning management system, virtual classroom, teachers and students) from five European universities. In the paper following aspects of the system are presented: concept and methodology of the Course Pool, technology for e-learning and evaluation results.